The Effect of Mind Mapping-Based Problem Based Learning Model on Mathematical Reasoning Ability in Terms of Self-Efficacy - Muh Khafid Wahyu Nugroho; Peduk Rintayati; Sandra Bayu Kurniawan (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
This study examines the effectiveness of Problem-Based Learning (PBL) integrated with Mind Mapping in improving elementary school students’ mathematical reasoning ability while considering the role of self-efficacy. Although previous studies have reported the benefits of PBL and Mind Mapping in mathematics education, limited research has investigated their combined implementation using a factorial experimental design that simultaneously examines the influence of self-efficacy on mathematical reasoning among elementary school students. To address this gap, the study employed a quantitative experimental method with a 2 × 2 factorial design involving 86 fifth-grade students from public elementary schools in Andong District, Boyolali Regency, Indonesia. Participants were assigned to either a PBL integrated with Mind Mapping group or a Direct Instruction group, while self-efficacy was classified into high and low categories. Data were collected using a mathematical reasoning test and a validated self-efficacy questionnaire and analyzed through descriptive statistics and Two-Way ANOVA. The findings revealed that students who learned through PBL integrated with Mind Mapping achieved significantly higher mathematical reasoning scores than those receiving Direct Instruction. Students with high self-efficacy also outperformed those with low self-efficacy, although no significant interaction was found between the learning model and self-efficacy. These results suggest that instructional strategies and self-efficacy independently contribute to mathematical reasoning development. This study provides empirical evidence supporting the integration of PBL and Mind Mapping as an effective approach to enhancing mathematics learning outcomes in Indonesian elementary schools.